Productivity and adaptability parameters of triticale for green feed in the steppe part of the Rostov region - A. V. Krokhmal’; E. A. Gordinskaya; N. I. Barulina (Зерновое хозяйство России)
The goal of the breeding program is to develop a variety with high productivity potential, capable of realizing this potential in a wide range of environmental conditions. The purpose of the work was to establish the features of the formation of the green forage crop, to estimate the adaptability of varieties and its individual parameters in the conditions of the steppe part of the Rostov region. The climate of the territory was arid, with uneven precipitation and frequent dry winds. The soil cover is represented by southern medium-deep clayey blackearth. The objects of the study were 6 winter varieties of feed triticale of the own breeding. The varieties were sown according to two forecrops, such as weedfree fallow to identify potential productivity opportunities, and millet to determine the capabilities of the variety in conditions close to production. There was found that the largest share of the effect on productivity range was of environmental conditions, 89.0 %, and only 4.6 % of the effect of the variety. The largest mean productivity over the years of study was formed by the variety ‘Styuard’ (90.1; maximum 104.5 t/ha) when laid in fallow, and the variety ‘Bemol 20’ (51.6; maximum 67.1 t/ha) when sown after millet. Green mass productivity is closely related to a number of stems per 1 m2 (r = 0.81). There was determined that during the studying period of green mass, stem stand per 1m2 ranged from 801 (‘Tornado’) to 954 pieces (‘Bemol 20’). By this period stem reduction of the varieties ‘Tornado’, ‘Styuard’, ‘Ariozo’ and ‘Bemol 20’ was 13–16 %, that of the varieties ‘Argo’ and ‘Agraf’ 26 % and 4 % respectively. The productivity range of the varieties when sown in fallow varied from 9.9 % (‘Ariozo’) to 19.5 % (‘Bemol 20’), it was twice as high when sown after millet, from 19.3 (‘Bemol 20’) to 30.3 % (‘Styuard’). Analysis of the adaptability parameters of the studied varieties allowed a comprehensive estimation of the adaptive properties of the varieties. Thus, the variety ‘Agraf’ had rank 1 in terms of stability (S2), ‘Styuard’ in terms of maximum productivity and genetic flexibility (GF), ‘Bemol 20’ in terms of average productivity in the entire set of environments, adaptation coefficient (AC). According to the sum of ranks of the main quantitative and qualitative indicators of adaptability, the variety ‘Argo’ was the best one (sum of ranks 20), with rank 1 for stress resistance (SR), homeostaticity (Hom), and breeding value of the genotype (Sc and GBVi).